Knowledge and awareness of emergency contraception among women undergoing medical termination of pregnancy in a tertiary care hospital in Andaman and Nicobar Islands - Barik, Shreya; Malakar, Abhishek; Khatuja, Ritu; Sahoo, Pinky S. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency contraception (EC) is a safe and cost effective measure, which when used judiciously can avoid unintended pregnancies. This is especially relevant in our country where both population control and unsafe abortions are a serious concern. For any contraceptive to be effective, the general population must have a proper knowledge and a positive attitude towards it. Women who come for medical termination of unwanted pregnancy are the best representatives of this and our study aimed to assess the knowledge and awareness of EC in this group. Methods: It was a descriptive, cross-sectional study conducted using a predesigned questionnaire among 100 women who came for medical termination of pregnancy at G. B. Pant Hospital, Port Blair. Questions were asked to evaluate their awareness, knowledge and attitude towards EC. Results: Out of 100 women, only 26 % had heard about EC, mostly from mass media, and seven of these 26 women had correct knowledge of timing of using EC. Four women had used EC before, whereas among others, fear of menstrual irregularity was the major deterrent. A significant association was found between education level and occupation with knowledge of EC. Conclusions: Although EC is a potent tool to avoid unwanted pregnancies, ignorance and misconceptions regarding EC is unfortunately still prevalent among those who would benefit the most from it. Medical personnel and health workers should be more proactive to propagate benefits of EC and encourage its use, as they are usually the first point of contact to the target population.